(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
Preparation of dough is one of the main stages of the technological process of bread production. The state and properties of the finished dough also determine the quality of the finished bread, due to which it significantly affects its state in the subsequent shaping, baking and baking processes.